Por uma ética de integridade e produção de sentidos na atenção a adolescentes infratores - Márcia Alves da Silva; Mirela Ribeiro Meira (EccoS – Revista Científica)
This text refers to an interdisciplinary academic research and extension that has being coordinated by the authors at the Centre for Socio-Educational Care (Case) in the city of Pelotas, Rio Grande do Sul, and aims to question the pedagogical, ethical and aesthetic processes with teenagers living in deprivation of liberty. This study originates in the field of social sciences and seeks to dialogue with the art and education in an attempt to understand the reality of special protection to adolescents in the country. The methodology adopted includes the universe of life stories. Our intention is to capture the narratives that treat life stories of young people from the organization and recording collective meetings with teenagers housed. Our intervention bet on workshops as collective creation as triggering a new ethic of dignity of life, where the productions trigger the context of the group, its expression level, since the workshops can be a “text” imbued with meanings and senses that cannot be overlooked as a source of data.